Analisis Produktivitas Pelayanan Petikemas Di Makassar New Port - Adhil Fauzan; M. Natsir Abduh; Savitri Prasandi Mulyani (Program Studi Teknik Sipil Universitas Bosowa, 2026)
This research aims to determine the productivity of container services at the container port (Makassar New Port) by analyzing the influence of equipment age, human resources and environmental factors on the productivity of container services at the Makassar New Port. This type of research is carried out with a quantitative approach using multiple linear regression analysis. The main data source comes from information obtained through direct observation at the research location and interviews. The research results show that partially and simultaneously the equipment age, human resources and environmental factors influence the productivity of container services at Makassar New Port.